AK4 promotes nasopharyngeal carcinoma metastasis and chemoresistance by activating NLRP3 inflammatory complex - Sai-Lan Liu; Li Yuan; Xue-Song Sun; Bei-Bei Xiao; Kai-Qi Lan; Zi-Jian Lu; Da-Feng Lin; Xiao-Yun Li; Jin-Jie Yan; Shu-Mei Yan; Qiu-Yan Chen; Lin-Quan Tang; et al. (Cell Death and Disease)
Abstract Metastasis is the main cause of treatment failure in nasopharyngeal carcinoma (NPC). Our previous study developed a transcriptomics-based gene signature (AK4, CPAMD8, DDAH1, and CRTR1) to predict metastasis in NPC and identify candidates that could benefit from induction chemotherapy (IC). Of these, adenylate kinase 4 (AK4) is a potent oncogene involved in the malignant progression of a variety of tumors. This study investigated the expression and mechanism of action of AK4, a member of the AK family of enzymes, in NPC. Quantitative real-time PCR, western blotting, and immunohistochemistry revealed that AK4 was upregulated in NPC and correlated with metastasis and chemoresistance. Stable ectopic overexpression of AK4 in NPC cell lines conferred resistance to taxol-induced apoptosis, promoted the migration, invasion, and EMT phenotype, and induced IL-1β secretion by activating the NLRP3 signaling pathway; knockdown of AK4 had the opposite effects. Mechanistically, AK4 co-localized with NNT, upregulated NLRP3 and IL-1β, and consequently altered NPC cell metastasis and chemoresistance. AK4 may play a role in the development of NPC and represent a potential therapeutic target.